Specific imaging features indicate the clinical features of patients with hepatic perivascular epithelioid cell tumor by comparative analysis of CT and ultrasound imaging - Gao, Xudong; Tang, Hewen; Wang, Jianying; Yao, Qian; Wang, Hong; Wang, Yan; Ma, Mingming; Yang, Wei; Yan, Kun; Wu, Wei (Frontiers in Oncology, 2022)
Objective: To explore the CT and ultrasound features and clinical significance of perivascular epithelioid cell tumor (PEComa) of liver. Methods: Eleven hepatic PEComa patients treated in our hospital were retrospectively analyzed based on the characteristics of the patients’ imaging results, including conventional ultrasound, CDFI, contrast-enhanced ultrasound (CEUS), and contrast-enhanced CT (CECT). Results: CT scans showed that all lesions were hypodense, the ultrasonography showed that lesions were either hyperechoic (4/11,36.36%), hypoechoic (4/11,36.36%), isoechoic (1/11,9.09%), or heterogeneously echoic (2/11, 18.18%). CDFI showed that most of the lesions had an abundant blood supply (9/11, 81.82%). Whether on CT scan or ultrasonography, the margins of the lesions were dominated by clear margins. Ultrasonography revealed more features: hyperechoic patterns around lesions (3/11, 27.27%), lateral shadow (5/11,45.45%). The CDFI showed that large blood vessels were observed around the lesions (9/11,81.82%). CECT shows two enhancement patterns: “fast in and fast out (FIFO)” (8/11,72.72%) and “fast in and slow out (FISO)” (3/11,27.27%). CEUS shows that all lesions were the enhancement pattern of “FISO”, which was different from CECT. All lesions displayed rapidly enhancement during HAP in CEUS during 7-20 s. Four patients (36.36%) washed out at 60 s-180 s, another four (36.36%) washed out at 180 s-300 s, and the remaining three patients (27.27%) showed no signs of washout even at 360s. Conclusion: Some imaging features, such as clear margins, peripheral hyperechoic around the lesion, lateral shadow, the large blood vessels around lesions and the “FISO” enhancement pattern, may indicate expansive growth of the tumor and be helpful in diagnosis of PEComa. Ultrasound images may provide more details for clinical reference.